Myxoid pleomorphic liposarcoma in the teres minor muscle: A case report. Issue 44 (4th November 2022) - Choi, Jun Ho; Lee, Soo Hyuk; Kim, Kwang Seog; Choi, Yoo Duk; Hwang, Jae Ha; Lee, Sam Yong
Abstract : Rationale: Myxoid pleomorphic liposarcoma (MPL) is a rare aggressive adipocytic tumor that mainly presents in children and adolescents. It is most frequently observed in the mediastinum and rarely in the head and neck, perineal region, or back. Herein, we report the first published case of MPL of the teres minor muscle. Patient concerns: A 24-years-old woman presented with a painless palpable mass in her right shoulder. Diagnoses: Magnetic resonance imaging identified a 9.0 × 7.0 × 4.0 cm mass suspected to be a sarcoma in the teres minor muscle. Positron emission tomography/computed tomography revealed no evidence of distant metastasis. Histopathological examination revealed the mass to be an MPL, which was assigned a histologic grade of 3 according to the French Federation of Cancer Centers Sarcoma Group system. No tumor cells were observed along the resected margins. Interventions: Under general anesthesia, the right teres minor muscle containing the mass was excised en bloc and frozen biopsy confirmed that the tumor cells did not invade the surrounding tissues. Outcomes: The patient underwent radiotherapy and was followed up for 6 months without complications. Lessons: Although MPL in the teres minor muscle is rare, it should be considered in the differential diagnosis in patients with a mass in the teres minor muscle due to its poor prognosis.